2008
DOI: 10.1161/circresaha.107.167395
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–Inducible Platelet-Derived Growth Factor-D Transcription Requires Specific Ser/Thr Residues in the Second Zinc Finger Region of Sp1

Abstract: Abstract-Sp1, the first identified and cloned transcription factor, regulates gene expression via multiple mechanisms including direct protein-DNA interactions, protein-protein interactions, chromatin remodeling, and maintenance of methylation-free CpG islands. Sp1 is itself regulated at different levels, for example, by glycosylation, acetylation, and phosphorylation by kinases such as the atypical protein kinase C-. Although Sp1 controls the basal and inducible regulation of many genes, the posttranslational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Mutation of Thr579 in the consensus CKII site did not eliminate CKII phosphorylation of Sp1, though it did perturb CKII's ability to inhibit Sp1 binding to DNA in vitro. Treatment of K562 cells with okadaic acid to inhibit endoge- We recently demonstrated that Thr668, along with Ser670 (and Thr681), is a target of phosphorylation by PKC-using a combination of approaches including in vitro peptide and protein phosphorylation analysis with Ala mutant counterparts, mass spectrometry phosphopeptide analysis, and coimmunoprecipitation analysis (63). This follows investigations by Pal et al demonstrating that PKC-binds to and phosphorylates the zinc finger region of Sp1 (49).…”
Section: Kinases Phosphorylating Sp1 Influence Its Dna Binding and Trmentioning
confidence: 70%
See 3 more Smart Citations
“…Mutation of Thr579 in the consensus CKII site did not eliminate CKII phosphorylation of Sp1, though it did perturb CKII's ability to inhibit Sp1 binding to DNA in vitro. Treatment of K562 cells with okadaic acid to inhibit endoge- We recently demonstrated that Thr668, along with Ser670 (and Thr681), is a target of phosphorylation by PKC-using a combination of approaches including in vitro peptide and protein phosphorylation analysis with Ala mutant counterparts, mass spectrometry phosphopeptide analysis, and coimmunoprecipitation analysis (63). This follows investigations by Pal et al demonstrating that PKC-binds to and phosphorylates the zinc finger region of Sp1 (49).…”
Section: Kinases Phosphorylating Sp1 Influence Its Dna Binding and Trmentioning
confidence: 70%
“…This is the first demonstration of phosphorylated Sp1 in diseased animal and human tissue (63). We previously showed that activated PKC-(pThr410) is also expressed in atherosclerotic plaques in the context of the Fas ligand (29).…”
Section: Kinases Phosphorylating Sp1 Influence Its Dna Binding and Trmentioning
confidence: 80%
See 2 more Smart Citations
“…Previous study had shown that angiotensin II by the angiotensin II type 1 receptor stimulates Sp1 phosphorylation and increases Sp1 binding to the PDGF-D [17,18]. PDGF-D by binding with the b-receptor but not areceptor [19,20] contributes to the pathophysiological process in the development and progression of cell proliferation and accumulation of extracellular matrix.…”
Section: Discussionmentioning
confidence: 98%